Relation between income inequality and mortality in Canada and in the United States: cross sectional assessment using census data and vital statistics. Issue 7239 (1st April 2000) - Ross, Nancy A; Wolfson, Michael C; Dunn, James R; Berthelot, Jean-Marie; Kaplan, George A; Lynch, John W
Abstract: Objective: To compare the relation between mortality and income inequality in Canada with that in the United States. Design: The degree of income inequality, defined as the percentage of total household income received by the less well off 50% of households, was calculated and these measures were examined in relation to all cause mortality, grouped by and adjusted for age. Setting: The 10 Canadian provinces, the 50 US states, and 53 Canadian and 282 US metropolitan areas. Results: Canadian provinces and metropolitan areas generally had both lower income inequality and lower mortality than US states and metropolitan areas. In age grouped regression models that combined Canadian and US metropolitan areas, income inequality was a significant explanatory variable for all age groupings except for elderly people. The effect was largest for working age populations, in which a hypothetical 1% increase in the share of income to the poorer half of households would reduce mortality by 21 deaths per 100 000. Within Canada, however, income inequality was not significantly associated with mortality. Conclusions: Canada seems to counter the increasingly noted association at the societal level between income inequality and mortality. The lack of a significant association between income inequality and mortality in Canada may indicate that the effects of income inequality on health are not automatic and may be blunted by the different ways in which social and economic resources are distributed in Canada and in the United States.